Murder at the Capitol : [large type] a Lincoln's White House mystery - Gleason, Colleen (Lincoln's White House mystery, 2020)
"On Independence Day, the citizens of Washington, DC, are celebrating as if there isn't a war. But the city is teeming with green Union recruits while President Lincoln and his War Department are focused on military strategy to take Richmond in Secessionist Virginia in order to bring the conflict to a swift end. Manassas, Virginia, near Bull Run Creek, is in their sights. The very next morning, as Congress convenes once more, a dead body is found hanging from the crane beneath the unfinished dome of the Capitol. Lincoln's close confidant, Adam Speed Quinn, is called upon to determine whether the man had taken his own life, or if someone had helped him. With the assistance of Dr. George Hilton and journalist Sophie Gates, Quinn investigates what turns out to be murder. But the former scout is about to be blindsided, for a Southern sympathizer in the city is running a female spy network reporting to the Confederacy, and she has an insidious plot to foil the Union Army's march to Manassas by employing the charms of one Constance Lemagne to get as close to Adam as possible "--